Genome-centered metagenomics illuminates adaptations of core members to a partial Nitritation–Anammox bioreactor under periodic microaeration - Shao, Yung-Hsien; Wu, Yu-Wei; Naufal, Muhammad; Wu, Jer-Horng (Frontiers in Microbiology, 2023)
The partial nitritation-anaerobic ammonium oxidation (anammox; PN-A) process has been considered a sustainable method for wastewater ammonium removal, with recent attempts to treat low-strength wastewater. However, how microbes adapt to the alternate microaerobic-anoxic operation of the process when treating low ammonium concentrations remains poorly understood. In this study, we applied a metagenomic approach to determine the genomic contents of core members in a PN-A reactor treating inorganic ammonium wastewater at loading as low as 0.0192 kg-N/m3/day. The metabolic traits of metagenome-assembled genomes from 18 core species were analyzed. Taxonomically diverse ammonia oxidizers, including two Nitrosomonas species, a comammox Nitrospira species, a novel Chloroflexota-related species, and two anammox bacteria, Ca. Brocadia and Ca. Jettenia, accounted for the PN-A reactions. The characteristics of a series of genes encoding class II ribonucleotide reductase, high-affinity bd-type terminal oxidase, and diverse antioxidant enzymes revealed that comammox Nitrospira has a superior adaptation ability over the competitors, which may confer the privileged partnership with anammox bacteria in the PN-A reactor. This finding is supported by the long-term monitoring experiment, showing the predominance of the comammox Nitrospira in the ammonia-oxidizing community. Metagenomic analysis of seven heterotrophs suggested that nitrate reduction is a common capability in potentially using endogenous carbohydrates and peptides to enhance nitrogen removals. The prevalence of class II ribonucleotide reductase and antioxidant enzymes genes may grant the adaptation to cyclically microaerobic/anoxic environments. The predominant heterotroph is affiliated with Chloroflexota; its genome encodes complete pathways for synthesizing vitamin B6 and methionine. By contrast, other than the two growth factors, Nitrospira and anammox bacteria are complementary to produce various vitamins and amino acids. Besides, the novel Chloroflexota-related ammonia oxidizer lacks corresponding genes for detoxifying the reactive oxygen species and thus requires the aid of co-existing members to alleviate oxidative stress. The analysis results forecast the exchanges of substrates and nutrients as well as the collective alleviation of oxidative stress among the core populations. The new findings of the genomic features and predicted microbial interplay shed light on microbial adaptation to intermittent microaeration specific to the PN-A reactor, which may aid in improving its application to low-strength ammonium wastewater.